2008
DOI: 10.3768/rtipress.2008.rr.0001.0802
|View full text |Cite
|
Sign up to set email alerts
|

Student Employment During the Transition to College in the United States

Abstract: In this paper, I use a nationally representative sample of American high school seniors in 1992 to examine change and stability in the employment patterns of youth as they make the transition from high school to college. Students with weak attachments to the labor force in high school tend to remain unemployed during the first year of college. Conversely, students who work in moderation while in high school have the highest odds of enrolling in college and working while doing so. Compared with their nonworking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Further, this report indicates that only a quarter of the students who attend part-time ultimately complete college, and students who are poor and/or students of color face additional barriers to completing their college educations. Bozic (2008) confirmed these results in his analysis of factors influencing the ability of students to complete their degree programs. Schools that have not been known for actively enrolling a significant amount of non-residential students are now recognizing that, whether they sought them out or not, the population of commuter students has increased at their universities and colleges.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Further, this report indicates that only a quarter of the students who attend part-time ultimately complete college, and students who are poor and/or students of color face additional barriers to completing their college educations. Bozic (2008) confirmed these results in his analysis of factors influencing the ability of students to complete their degree programs. Schools that have not been known for actively enrolling a significant amount of non-residential students are now recognizing that, whether they sought them out or not, the population of commuter students has increased at their universities and colleges.…”
Section: Introductionmentioning
confidence: 54%
“…Another problem highlighted in the literature is that commuting students had the least amount of economic resources. Bozic (2008) also found that students who worked 20 hours a week or more and who lived at home were more likely to leave college during their freshman year. Bozick found that students from low-income families are more likely to work for school-related expenses and to live at home during the first year of college.…”
Section: Differences Between Skills/qualities Of Residential and Commuter Studentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study by Kuh et al (2001) also show that commuters have less level of interaction with faculty. All these negative effects of commuting may finally lend themselves to students who are less committed to completing their education, a concern clearly made by Lumina's foundation study and proven by other studies (Bozic, 2008).…”
Section: Millennials/gen Z Life and Learning Stylesmentioning
confidence: 99%
“…An additional dimension highlighted by Bozic (2008) about commuters is the aspect of commuters being economically disadvantaged compared to their peers. This is because students that come from low-income families were seen to work, as well as live at home during their freshman year.…”
Section: Millennials/gen Z Life and Learning Stylesmentioning
confidence: 99%